2020
DOI: 10.1101/2020.06.04.132571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered Huntingtin-Chromatin Interactions Predict Transcriptional and Epigenetic Changes in Huntington’s Disease

Abstract: SummaryProgressive striatal gene expression changes and epigenetic alterations are a prominent feature of Huntington’s disease (HD), but direct relationships between the huntingtin (HTT) protein and chromatin remain poorly described. Here, using chromatin immunoprecipitation and sequencing (ChIP-seq), we show that HTT reproducibly occupies specific locations in the mouse genome, including thousands of genomic loci that are differentially occupied in striatal tissue from a knock-in mouse model of HD (B6.HttQ111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Thus, many of the transcriptional effects of mHTT may be mediated by PRC2 loss-of-function. Consistent with this idea, we recently described a global decrease of H3K27me3 levels in striatal tissue from HD knock-in mice 38 . Future studies should test whether restoring PRC2 function can rescue the phenotypic consequences of HD mutations.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, many of the transcriptional effects of mHTT may be mediated by PRC2 loss-of-function. Consistent with this idea, we recently described a global decrease of H3K27me3 levels in striatal tissue from HD knock-in mice 38 . Future studies should test whether restoring PRC2 function can rescue the phenotypic consequences of HD mutations.…”
Section: Discussionsupporting
confidence: 62%
“…The HTT protein has genotype-specific interactions with PRC2 in vitro 15 and in vivo 38 , and conditional knockout of PRC2 in striatal MSNs causes gene expression changes that mimic the effects of HD mutations 39 . To test whether dysregulated cell type identity modules in Htt Q175/+ mice involve PRC2, we assembled nine ChIP-seq datasets profiling the genomic occupancy for components of the PRC2 complex (EZH2, SUZ12) or for H3K27me3 in four disease-relevant cell types: medium spiny neurons 38,39 , astrocytes 40 , oligodendroocytes 27 , and embryonic stem cells 40,41 . We tested for over-representation of each of our 77 gene co-expression modules among putative PRC2 target genes, defined by the presence of a PRC2-related ChIPseq peak +/-5kb from a gene's transcription start site.…”
Section: Network Analyses Reveal Principles Of Transcriptional Dysregmentioning
confidence: 99%
“…Otherwise, we downloaded aligned sequence reads, performed peak-calling with MACS v2.1 (Zhang et al, 2008), and annotated peaks to genes with transcription start sites within 65 kb. The nine datasets are as follows: (1) ChIP-seq of EZH2 in mouse embryonic stem cells (Kloet et al, 2016), obtained from ChEA (Lachmann et al, 2010); (2) ChIP-seq of SUZ12 in mouse embryonic stem cells (Kloet et al, 2016), obtained from ChEA (Lachmann et al, 2010); (3) ChIP-seq of H3K27me3 in mouse embryonic stem cells, generated by Bing Ren's lab (UCSD) for the ENCODE consortium (ENCFF055QNY); (4) ChIP-seq of H3K27me3 in mouse MSNs (Von Schimmelmann et al, 2016), obtained from HDSigDB; (5) ChIP-seq of H3K27me3 in bulk striatal tissue from four-month-old Htt Q111/1 and Htt 1/1 mice (Pearl et al, 2020); (6) ChIP-seq of EZH2 in human astrocytes, generated by Bradley Bernstein's lab for the ENCODE consortium (reproducible peaks from ENCFF254DFD and ENCFF831JFC); (7) ChIP-seq of H3K27me3 in human astrocytes, generated by Bradley Bernstein's lab for the ENCODE consortium (ENCFF315BVX); (8) ChIP-seq of EZH2 in mouse corpus callosum (enriched for oligodendrocytes; Bardile et al, 2019; their Table S3); (9) ChIP-seq of EZH2 in mouse corpus callosum (enriched for oligodendrocytes; Bardile et al, 2019; their Table S3). We tested for over-representation in gene co-expression modules using Fisher's exact tests.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…et al, 2011 Alternative splicing Aberrant: dysregulated TRANS-splicing factors (PTBP1, SRSF6) b . Mutant HTT mRNA sequesters spliceosome components, dysregulating splicing, and causing toxicity g Sathasivam et al, 2013;Lin et al, 2016;Schilling et al, 2019 Epigenetics Preferentially closed chromatin state and transcriptional repression: reduced histone acetylation, increased histone methylation e,f , decreased AcH3 levels, decreased number of genes bound by AcH3 f , increased H3K27me3 and decreased H3K4me3 e Ferrante et al, 2003;Stack et al, 2007;Luthi-Carter et al, 2010;Seong et al, 2010;McFarland et al, 2012;Biagioli et al, 2015;Hervás-Corpión, 2018;Pearl et al, 2020 Dopamine signaling b Altered dopamine signaling has been associated with behavioral alterations observed in HD. Dopamine levels are increased at early stage and decreased at later stage Chen et al, 2013;Koch and Raymond, 2019 Somatic CAG instability b Increased in striatum and cerebral cortex Telenius et al, 1994;Swami et al, 2009 Electrophysiology d Changes in the balance of excitatory and inhibitory inputs to the direct and indirect pathway MSNs Galvan et al, 2012 *Abbreviations are indicated with superscript numbers, models used in the studies with superscript letters.…”
Section: Pathogenic Mechanisms Of the Hd Mutation In Striatal Districmentioning
confidence: 99%
“…et al, 2011 ; Table 1 ). Notably, mutant huntingtin can directly or indirectly compromise the epigenetic status of brain cells ( Table 1 ), at least in part explaining the observed transcriptional dysregulation ( Stack et al, 2007 ; Seong et al, 2010 ; McFarland et al, 2012 ; Biagioli et al, 2015 ; Hervás-Corpión, 2018 ; Pearl et al, 2020 ).…”
Section: Pathogenic Mechanisms Of the Hd Mutation In Striatal Districmentioning
confidence: 99%